Structural insights into endogenous ligand selectivity and activation mechanisms of FFAR1 and FFAR2 - Yudun Ke; Yimiao Huang; Cuiying Yi; Limin Ma; Xiaojing Chu; Beili Wu; Qiang Zhao; Shuo Han (Cell Reports)
Summary: Free fatty acid receptors (FFARs) play critical roles in metabolic regulation and are potential therapeutic targets for metabolic and inflammatory diseases. A comprehensive understanding of the activation mechanisms and endogenous ligand selectivity of FFARs is essential for drug discovery. Here, we report two cryoelectron microscopy structures of the human FFAR1 bound to the endogenous ligand docosahexaenoic acid (DHA) and Gi1 protein as well as FFAR2 in complex with butyrate and Gi1 at 3.2 Å and 3.3 Å resolution, respectively. These structures highlight that distinct locations and sizes of the orthosteric ligand binding pockets are crucial determinants of the endogenous ligand selectivity of this receptor subfamily. Additionally, computational analysis reveals a potential allosteric ligand binding pocket in FFAR2. Furthermore, we observe that the upward movement of helix V upon endogenous ligand binding is responsible for receptor activation. These insights will significantly aid in the development of drugs targeting this receptor family.